An analysis of the study habits of students in tertiary institutions. - Koh, Hong Eng. (2008)
This research attempts to explore and investigate any significant differences in the study habits of students in higher education. Based on the study habits questionnaire design by Bragstad and Stumpf, seven study habits are examined. They are concentration, listening and taking notes, motivation, organising time, remembering, studying a chapter and taking tests.